The effects of astaxanthin on salivary gland damage caused by cisplatin in the rat - Terzi, Suat; Özgür, Abdulkadir; Mercantepe, Tolga; Çeliker, Metin; Tümkaya, Levent; Dursun, Engin (International Journal of Research in Medical Sciences, 2017)
Background: Cisplatin is a potent antineoplastic agent widely used for a variety of malignancies. However, it has many dose-limiting side effects such as neurotoxicity, cytotoxicity and ototoxicity. The aim of our study was to determine the effectiveness of astaxanthin (ASX) as a cytoprotective agent against cisplatin-induced cytotoxicity in the submandibular glands of rats. Methods: Thirty-six adult male Wistar albino rats were divided into six groups as follows: group I: saline control; group II: 75 mg/kg/day ASX; group III: 16 mg/kg cisplatin; group IV: 25 mg/kg/day ASX + cisplatin; group V: 75 mg/kg/day ASX + cisplatin; group VI: olive oil + cisplatin. In all groups, submandibular gland histopathological and histochemical investigations were done using a light microscope. Every rat section was semi-quantitatively scored. Neutrophil infiltration density, myoepithelial cell density in the degeneration area, degenerative granular duct cell density, degenerative seromucous acinus cell density, and changes in the content of the secretory granules of seromucous acini and granular ducts of the parenchyma and stroma were calculated. Results: The results of the analysis of the mean acinus area of the submandibular gland revealed that there was a significant decrease in cisplatin group rats when compared to control rats (p<0.05, p=0.00). However, there was no significant difference between-group IV, V and control group in terms of mean acinus area. (p=0.541, p=0.773). The results of the analysis of the mean ducts area of the submandibular gland also showed that there were significant increased group III compared to control rats (p<0.05, p=0.031). There was no significant difference between-group IV, V and control group in terms of mean ducts area (p>0.05, p=0.921). Similarities were observed in the mean ducts area with the group IV and the group V (p>0.05, p=0.571). Conclusions: These results suggest the possibility that the clinical use of ASX could reduce or prevent damage to the salivary gland of patients receiving cisplatin chemotherapy.